Overview of Immune Perspectives and Current Treatment Strategies against COVID-19 - Awais, Muhammad; Naveed, Muhammad; Mansoor, Sajid; Zafar, Rimsha; Riaz, Rabia (BioScientific Review, 2021)
COVID-19 is a highly infectious respiratory disorder, affecting millions with about 10% fatality rate. Infected patients may be symptomatic and show mild to severe symptoms, manifesting as mild fever, cough, headache, and nausea or they may remain asymptomatic, showing no symptoms at all. World Health Organization (WHO) reported over 260, 493 573confirmed cases worldwide with 5 195, 354deaths (November 2021). There are myriads of promising approaches to pharmacologically treat severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the newly reported seventh human coronavirus responsible for the COVID-19 pandemic. There are various types of potential drugs, such as monoclonal antibodies, interferon therapies, peptides, small molecule drugs, oligonucleotides, and vaccines, under consideration to target various structural components of the virus. This study focused on reviewing potential drug candidates, namely remdesivir, lopinavir, emetine, aloxistatin, viracept, homoharringtonine, ivermectin, favipiravir, tocilizumab, chloroquine, and leronlimab that can be used to treat COVID-19 infection. These drugs target the membrane nucleocapsid, spike, or envelope proteins, and are either in clinical trials or are under consideration. These drugs directly inhibit the viral infection, while others trigger the immune system to fight against the virus. We also overviewed the immunization ability of in-use and accepted vaccines, such as Pfizer and Moderna. It was followed by a review of research dealing with the immune system and how it tries to manage the infection as well as vaccines and potential therapeutic agents. Keywords: adaptive immune response, COVID-19, innate immune response, SARS-CoV-2, therapeutic drugs, vaccine Copyright(c) The Authors